Microsoft Office 2007 - Shelly, Gary B. (Thomson/Course Technology, 2008)
Introduce your students to the new generation of Microsoft Office with the new generation of Shelly Cashman Series books! For the past three decades, the Shelly Cashman Series has effectively introduced computer skills to millions of students. With Windows Vista, we're continuing our history of innovation by enhancing our proven pedagogy to reflect the learning styles of today's students. In Microsoft Windows Vista: Introductory Concepts and Techniques you'll find features that are specifically designed to engage students, improve retention, and prepare them for future success. Our trademark step-by-step, screen-by-screen approach now encourages students to expand their understanding of the Windows Vista operating system through experimentation, exploration, and planning ahead. Brand new end of chapter exercises prepare students to become more capable users by requiring them to use critical thinking and problem-solving skills.